1993
DOI: 10.1080/00288233.1993.10427489
|View full text |Cite
|
Sign up to set email alerts
|

Effects of cultivar introduction and fertiliser on characteristics of white clover (Trifolium repensL.) plants and populations in a hill pasture

Abstract: Pastures based on the white clover cultivars Grasslands Tahora and Grasslands Huia ",:ere established by oversowing into unimproved hIll country at Ballantrae in May-June 1986. Each pasture type occupied 2.2 ha, and a further 2.2 ha of unamended pasture containing the resident clover ecotype was also included. From August 1988, four ferti1i~er treatments (control, receiving no fertiliser; reactive phosphate rock; partially acidulated phosphate rock; and a superphosphate/phosphate rock blend, the latter three a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…The experiment was conducted on moderate-steep hill land at Ballantrae Hill Country Research Station, 20 km NE of Palmerston North in the lower North Island of New Zealand. Details of the site and experimental design were presented by Chapman et al (1993b). The mean annual rainfall at the site is 1270 mm, and average temperature is 12.8°C.…”
Section: Site and Experimental Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The experiment was conducted on moderate-steep hill land at Ballantrae Hill Country Research Station, 20 km NE of Palmerston North in the lower North Island of New Zealand. Details of the site and experimental design were presented by Chapman et al (1993b). The mean annual rainfall at the site is 1270 mm, and average temperature is 12.8°C.…”
Section: Site and Experimental Designmentioning
confidence: 99%
“…The genetic composition of the white clover plant populations in all Huia-sown and Tahora-sown plots was measured in January 1990 and January 1994 using cyanogenesis as a genetic marker. A full description of the technique can be found in Chapman et al (1993b), which also reports data from the January 1990 sampling. In essence, the resident white clover ecotype, Huia and Tahora all had sufficiently different frequency occurrence of cyanogenesis to allow resident and Huia plants be distinguished from each other in the Huiasown treatment, and resident and Tahora plants to be distinguished in the Tahora-sown treatment.…”
Section: Sward and Plant Measurementsmentioning
confidence: 99%
See 1 more Smart Citation
“…Attempts to increase the clover yield of hill country pastures through the introduction of new genotypes have been largely unsuccessful (Barker et al 1988;Macfarlane et al 1990b;Webby et al 1990;Wedderburn et al 1996;Dodd et al 2001) with few exceptions (see Chapman et al 1993). Either the new high-productivity genotypes have failed to persist, or the new persistent genotypes have shown no productivity gains over the resident ecotypes.…”
Section: Productive Performance Depends On the Genotypic Basementioning
confidence: 99%
“…Numerous field studies have demonstrated an improvement in pasture production and forage quality as a result of introducing both grasses and legumes into hill-country pastures (e.g., Wedderburn et al 1996), but also by introducing clover only into existing swards (e.g. Lambert et al 1986;Chapman et al 1993). The rationale for this approach is based on the role of the legume in improving the nitrogen economy of the soilpasture system, as a pre-requisite to establishing grasses of high productive potential (Ledgard et al 1987).…”
Section: Introductionmentioning
confidence: 99%